Functional-Semantic and Derivative Signs of Nominations of Covid and its Synonymic Correspondents in the Latest Media Discourse - Kostusiak, Nataliia; Navalna, Maryna; Levchenko, Tetiana; Grozian, Nina; Pryimachok, Oksana; Prudnykova, Tetiana (My University, 2021)
The article focuses on borrowed tokens, a significant non-verbal factor in the use of which was a viral disease. On the basis of sentence constructions selected from the latest media journalism, the functional-semantic potential of the international abbreviation COVID-19 is determined, as well as its semantic variants covid, coronavirus, and names of strains which have undergone phonetic and morphological adaptation to the norms of modern Ukrainian literary language. The focus is made on secondary nominations, endowed with a negative color. The role of the analyzed borrowings in the modeling of statements related to decoding is determined, their purpose is to serve as a means of subjective expression of the text is revealed, their intention to actualize the reader's attention and implement evaluative, expressive, media-appellate and other functions. It is noted that the activity of nominations of viral disease and its varieties is one of the important prerequisites for the production of neoderivatives based on them (juxtaposites and suffix and prefixal new formations), which are characterized by a wide range of uses, inter thematic movements, partly graphic variance, which indicates the ongoing process of establishing of these nominations in the Ukrainian language.
Keywords: adjective; application; derivation; emotionally-expressive coloring; extralinguistic factors; mass media; noun; vocabulary